Identification and functional analysis of novel SOX11 variants in Chinese patients with Coffin-Siris syndrome 9 - Ding, Yu; Chen, Jiande; Tang, Yijun; Chen, Li-Na; Yao, Ru-En; Yu, Tingting; Yin, Yong; Wang, Xiumin; Wang, Jian; Li, Niu (Frontiers in Genetics, 2022)
SOX11 is a transcription factor belonging to the sex determining region Y-related high-mobility group box family that plays a vital role in early embryogenesis and neurogenesis. De novo variants in SOX11 have been initially reported to cause a rare neurodevelopmental disorder, mainly referred to Coffin-siris syndrome 9 (CSS9, OMIM# 615866) which is characterized with growth deficiency, intellectual disability (ID), microcephaly, coarse facies, and hypoplastic nails of the fifth fingers and/or toes. A recent large-scale cohort study suggests that SOX11 variation would result in a clinically and molecularly distinct disease from CSS. Here, we describe three unrelated Chinese cases with variable phenotype, mainly involving DD, ID, short statute, microcephaly, facial deformities (i.e., prominent forehead, arched eye brow, flat nasal bridge, broad nose and short philtrum), and cryptorchidism. Whole-exome sequencing (WES) revealed three novel heterozygous variants in the SOX11 gene, including two missense variants of c.337T>C (p.Y113H) and c.425C>G (p.A142G), and one nonsense variant of c.820A>T (p. K142*). Luciferase reporting assay shows that the two missense variants impair the transcriptional activity of the SOX11 target gene GDF5. Additionally, WES uncovered a 4,300 kb deletion involving the region of 1q24.2-q25.1 (hg19，chr1:169,433,149-173,827,682) in patient 1, which also contributes to the condition of the patient. In summary, this is the first report of Chinese cases with de novo variants of SOX11. Our study partially supports the previous observation that the phenotype caused by SOX11 variants somewhat differs from classical CSS.